Processo oxidativo avançado (UV/H2O2) como alternativa de pré-tratamento de efluente contaminado pelo agrotóxico clorpirifós. - BERNARDELLI, P. V. (2018)
Brazil has become the world?s top pesticide consumer since 2008. This high consumption rate could lead to serious environmental, sanitary and social risks. Given this, mitigating practices play a fundamental role to reduce the impact caused by pesticide use. Among these, a bioreactor known as Biobed stands out. However, some specific pesticides interfere negatively on that reactor, consequently diminishing its efficiency. In this context, the Advanced Oxidation Process UV/H2O2 proves to be an interesting pretreatment alternative, as it has shown to be effective for different pesticides degradation. The aim of this study was to evaluate UV/H2O2 technology as a chlorpyrifos pretreatment, in order to determine the pre-oxidation conditions. The photodegradation was carried out in an annular reactor, with a high pressure UV lamp. Tests were performed with the initial H2O2 concentration varying from 600 to 2000 mg/L and reaction time from 15 to 80 minutes, while the lamp was powered both with 80 and 125W. The best result was obtained using 125W, H2O2 concentration of 1750 mg/L and 80 minutes of pre-oxidation, providing a 31.5% removal. These results show that UV/H2O2 technology is efficient as a pretreatment technique, resulting in a less concentrated and toxic effluent, so it could be further degraded by bioreactors. Palavras-chave: Pré-tratamento, UV/H2O2 , Biobed